PENGARUH MOTIVASI KERJA, STRES KERJA, DAN QUALITY OF WORK LIFE TERHADAP KINERJA KARYAWAN PT SANKYU INDONESIA INTERNATIONAL KRAKATAU STEEL IN SITE CILEGON - Siti Salma Raudhotunnisa; Renny Husniati (Jurnal Akuntansi dan Pajak, 2022)
This research is a quantitative study that intends to find out and prove whether there is an influence between work motivation, work stress, and quality of work life on the performance of employees at PT Sankyu Indonesia International Krakatau Steel In Site Cilegon, either partially or simultaneously. The population in this study were employees of level R2 with a sample of 85 employees obtained through the saturated sampling technique. Data was obtained through the distribution of questionnaires with google form. The analytical techniques applied in this research are the descriptive analysis technique and inferential analysis using the SMARTPLS 3.2.9 statistical test tool. Meanwhile, the hypothesis test is t-test and f-test using a significance level of 5% (0.05). The results of this study indicate (1) work motivation has a positive and significant effect on employee performance; (2) work stress has a positive and significant effect on employee performance; (3) Quality of Work Life has a positive and significant effect on employee performance; (4) Work motivation, work stress, and quality of work life simultaneously affect employee performance.